Taxonomic review of the Afrotropical genus Gracililema Krüger with descriptions of three new species (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Volynkin, Anton V. (Zootaxa, 2022)
The footman moth genus Gracililema Krüger, 2015 is reviewed and three new species are described: Gracililema bettoni sp. n. (Kenya and Ethiopia), G. lydiae sp. n. (northern Mozambique, Zimbabwe, Zambia, Tanzania, Kenya and Ethiopia) and G. smithi sp. n. (southern Mozambique and eastern South Africa). Adults, except the unknown male of G. proleucodes (Kiriakoff, 1958), together with male and female genitalia of all Gracililema species are illustrated.